Shear induced diffusion in dense granular flows - Orpe, Ashish V.; Rycroft, Chris H.; Kudrolli, Arshad A. (IUTAM-ISIMM Symposium on Mathematical Modeling and Physical Instances of Granular Flows, 2010)
The dynamics of dense granular flows subjected to gravity induced shear are investigated experimentally using the refractive index matching technique. The system consists of grains flowing inside a bin with a rectangular cross-section and sheared by a rough boundary on one side and smooth boundaries on the remaining sides. The particles flow within a viscous interstitial liquid having the same refractive index as particles and are imaged in the bulk using laser fluorescence. The particle positions are identified very accurately and tracked over long durations to obtain the mean and fluctuating properties. The shear is observed to be non-linear and localized in a region of 3 to 4 particles near the boundary. The boundary imposes a packing order, and the grains are observed to flow in layers, parallel to the shearing boundary, which get progressively more disordered with distance from the walls. We have also carried out soft particle simulations in a equivalent system incorporating the Cundall-Strack contact model between the particles and ignoring the hydrodynamic effects of the interstitial liquid to understand the effect of particle friction coefficient, elasticity, contact model and polydispersity on the mean and fluctuating flow properties. We find the mean velocity and the number density of the particles as a function of flow cross-section and the particle fluctuation properties observed in the experiments and the simulations to in very good agreement after appropriate scaling.
Keywords: DEM; Diffusion; granular; index matching; LAMMPS; laser fluorescence